AI-ENHANCED COUNTER-OFFENSIVE DECISION-MAKING IN HYBRID WARFARE - Babanov, Vladimir (E-Journal VFU, 2026)
In this article the use of artificial intelligence (AI) is being explored as a method for enhancing counter-offensive decision making within hybrid warfare environment. It is defined as an area where the intersection of conventional military tactics and other forms of warfare, such as cyber warfare, information warfare and psychological warfare, occur. Hybrid warfare creates conditions of uncertainty, urgency and high levels of asymmetry which necessitates effective and timely decision-making. The research demonstrates that the use of AI may provide enhanced support for counter-offensive planning by reducing decision cycle time, providing support for the integration of multiple domain data and by enhancing situational awareness using analytical tools and decision-support systems. The research identifies the benefits of AI enabled decision-making but also points out the existing limitations. It concludes that AI could be most effective when used as part of a balanced human-machine system whereby AI provides support for data driven decision-making processes and humans maintain strategic judgment and accountability.
Keywords: artificial intelligence; hybrid warfare; cyberwarfare; security policy; defense policy